GOCC-beluga whale genetic data - O'Corry-Crowe, Greg; Suydam, Robert; Quakenbush, Lori; Potgieter, Brooke; Harwood, Lois; Litovka, Dennis; Ferrer, Tatiana; Citta, John; Burkanov, Vladimir; Frost, Kathy; Mahoney, Barbara (Dryad Digital Repository, 2018)
contains detailed genetic data on beluga whales, including GenBank accession numbers, mtDNA haplotype frequencies and microsatellite locus allele frequencies